(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research population represents the banks listed in the Iraq Stock Exchange, while the research sample is represented by (5) banks chosen from among (25) banks listed in the Iraq Stock Exchange, represented by (Assyria International Bank, Bank of Baghdad, Gulf Commercial Bank, Bank Commercial Region, Trans-Iraq Investment Bank) that matches the research requirements for the period (2015_2022) using annual data. A set of financial ratios was used to measure each financial soundness indicator, and statistical methods represented by measures of central tendency were used, as the (arithmetic mean) was used to know the rank of each bank during the analysis, the highest value, the lowest value, and the rank of each bank among the banks investigated. The research concluded that there is The effect of financial soundness indicators in enhancing the volume of bank deposits, and this effect varies from one bank to another during the research period. On the other hand, the study recommended the need for banks to evaluate financial soundness indicators and develop them continuously to keep pace with the changes occurring in the economic environment to enhance the volume of deposits, which will reflect positively on the financial soundness of the banking sector and the economy